Cost optimality and nZEB target in building renovation of Portuguese residential buildings - Almeida, Manuela Guedes de (2014)
Promoting the improvement of the overall energy performance of buildings is a relevant part of the European climate action and the Roadmap for moving towards a competitive low carbon economy in 2050, with an expectation of reducing greenhouse gas (GHG) emissions by around 90% when compared to 1990 values, in the area of the built environment. The recast of the European Energy Performance of Buildings Directive (EPBD) introduced the goal of nearly zero-energy buildings (nZEB) for all new buildings from January 1st, 2021 and plans should be drawn to stimulate the transformation of existing buildings that are refurbished into the same concept. EPBD also requires that all European Member States must ensure that the minimum energy performance requirements for buildings are set to achieve optimal levels, i.e. the energy performance levels that lead to the minimum cost during the life cycle. Therefore, Cost Optimality and nZEB are two fundamental concepts within the current European Union policy related to the energy performance of buildings and consequently related to climate change mitigation and non-renewable resources consumption, with Cost Optimality mainly focused on costs and nZEB focused on low energy consumption levels and on site renewables harvesting. In this context, this paper, using two characteristic buildings of the Portuguese residential building stock, aims at presenting the results that emerged from the analysis and identification of the most cost-effective packages of renovation measures needed to adapt existing buildings to zero energy balance and comparing them with those resulting from the calculation of cost-optimal levels.The investigation of the trade-offs between a renovation towards zero energy balance and a cost optimal renovation without energy use restrictions is relevant to provide clues to the development of national plans for increasing the number of nZEB and to provide appropriate financing and other instruments to catalyze this transformation.